Costs of remote monitoring vs. ambulatory follow-ups of implanted cardioverter defibrillators in the randomized ECOST study. Issue 8 (9th March 2014) - Guédon-Moreau, Laurence; Lacroix, Dominique; Sadoul, Nicolas; Clémenty, Jacques; Kouakam, Claude; Hermida, Jean-Sylvain; Aliot, Etienne; Kacet, Salem; ,
Abstract : Aims: The Effectiveness and Cost of ICD follow-up Schedule with Telecardiology (ECOST) trial evaluated prospectively the economic impact of long-term remote monitoring (RM) of implantable cardioverter defibrillators (ICDs). Methods and results: The analysis included 310 patients randomly assigned to RM (active group) vs. ambulatory follow-ups (control group). Patients in the active group were seen once a year unless the system reported an event mandating an ambulatory visit, while patients in the control group were seen in the ambulatory department every 6 months. The costs of each follow-up strategy were compared, using the actual billing documents issued by the French health insurance system, including costs of (i) (a) ICD-related ambulatory visits and transportation, (b) other ambulatory visits, (c) cardiovascular treatments and procedures, and (ii) hospitalizations for the management of cardiovascular events. The ICD and RM system costs were calculated on the basis of the device remaining longevity at the end of the study. The characteristics of the study groups were similar. Over a follow-up of 27 months, the mean non-hospital costs per patient-year were €1695 ± 1131 in the active, vs. €1952 ± 1023 in the control group ( P = 0.04), a €257 difference mainly due to device management. The hospitalization costs per patient-year were €2829 ± 6382 and €3549 ± 9714 in the active and control groups, respectively ( P = 0.46). Adding the ICD to the non-hospital costs, the savings were €494 ( P = 0.005) or, when the monitoring system was included, €315 ( P = 0.05) per patient-year. Conclusion: From the French health insurance perspective, the remote management of ICD patients is cost saving. Clinical trials registration: NCT00989417, www.clinicaltrials.gov